NET balancing: a problem in inflammatory lung diseases - Cheng, Olivia Z.; Palaniyar, Nades (Frontiers in Immunology, 2013)
Neutrophil extracellular traps (NETs) are beneficial antimicrobial defense structures that can help fight against invading pathogens in the host. However, recent studies reveal that NETs exert adverse effects in a number of diseases including many lung diseases. Most of the inflammatory lung diseases are characterized with a massive influx of neutrophils into the airways. Neutrophils contribute to the pathology of these diseases. To date, NETs have been identified in the lungs of cystic fibrosis, acute lung injury, allergic asthma and lungs infected with bacteria, virus, or fungi. These microbes and several host factors can stimulate NET formation, or NETosis. Different forms of NETosis have been identified; these NETotic pathways are dependent on the types of stimuli. All of these pathways however appear to result in the formation of NETs with DNA, modified extracellular histones, proteases and cytotoxic enzymes. Some of the NET components are immunogenic and damaging to the host tissue. Innate immune collectins such as pulmonary surfactant protein D (SP-D) binds NETs, and enhances the clearance of dying cells and DNA by alveolar macrophages. In many inflammatory lung diseases, bronchoalveolar SP-D levels are altered and its deficiency results in the accumulation of DNA in the lungs. Some of the other therapeutic molecules under consideration for treating NET-related diseases include DNases, antiproteases, myeloperoxidase inhibitors, peptidylarginine deiminase-4 inhibitors and anti-histone antibodies. Too much of the good thing can be a bad thing. Maintaining the right balance of NET formation and reducing the amounts of NETs that accumulate in the tissues are essential for harnessing the power of NETs with minimal damage to the hosts.